Absence of Tolerance to Cefoxitin in Anaerobic Bacteria - Goldstein, Ellie J. C. (1981)
None of the 46 strains of anaerobic bacteria tested, including 26 strains of Bacteroides fragilis, showed tolerance (minimal bactericidal concentration/minimum inhibitory concentration ratio >32) to cefoxitin.